Community Structure of Gastropods in the Intertidal Zone of Tanjung Kelor Beach, Sekotong, West Lombok, Indonesia - Lisa Febriyani; Imam Bachtiar; Lalu Japa (Jurnal Biologi Tropis, 2026)
Tanjung Kelor Beach, located in Sekotong, West Lombok, is an intertidal area with high biological potential that supports coastal tourism development. However, information regarding the community structure of Gastropods in this area remains limited. This study aimed to analyze the abundance and species composition of Gastropods, family richness, and ecological indices: species diversity, evenness, and dominance indexs. Data were collected using the transect–quadrant method, with three transects placed perpendicular to the shoreline and a total of 30 quadrats measuring 1 × 1 m². The results revealed the presence of 17 Gastropod species belonging to 9 families, with a total of 1,209 individuals recorded. The community of Gastropod composition was dominated by the family Strombidae (43.09%) at the family level and Strombus urceus (15.72%) at the species level. Nerita undata (8.44%) wasa species consistently found at all stations across three substrate types: muddy, sandy, and seagrass beds. The diversity index (H’) was categorized as moderate (1.75–1.93), the evenness index (E) ranged from moderate to high (0.70–0.93), while the dominance index (C) indicated low values (0.17–0.20). These findings are expected to provide a scientific basis for coastal ecosystem conservation management and the development of educational tourism at Tanjung Kelor Beach.